SISTEM INFORMASI MANAJEMEN INVENTORI JJ CAFE (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2022)
This study aims to find out the problems that exist in JJ Cafe so that an information system is designed to help facilitate work in managing goods so that there are no more mistakes. The research method here uses a descriptive method using the help of an object-oriented system approach (Object Oriented). The results of this study discuss the system that has been created by displaying the images that exist in the system. With the inventory management information system, it is expected to be able to meet the needs of JJ Cafe with no more errors in inputting inventory data, purchasing goods and returns, and sales, so that work will be easier, faster in making reports and stock information can be known. with the help of the application.